Adaptive stabilisation of random systems with arbitrary switchings. Issue 18 (1st December 2015) - Jiao, Ticao; Xu, Shengyuan; Li, Yongmin; Li, Ze
Abstract : This study is concerned with the global stabilisation problem for a class of random non‐linear systems with arbitrary switchings and parameter uncertainties. Under some milder assumptions and by constructing a Lyapunov function, a common adaptive state feedback controller is designed such that the resulting closed‐loop system has a globally unique and almost surely bounded solution. Furthermore, the system states are exponentially noise‐to‐state stable in mean square. Finally, the efficiency of the proposed design approach is demonstrated by a numerical example.